Electrospray Ionization-Ion Trap Mass Spectrometry Study of PQAAPro and PQProAA Mimetic Derivatives of the Antimalarial Primaquine - Nuno Vale (2008)
Electrospray ionization-ion trap mass spectrometry (ESI-MS) of imidazolidin-4-one peptidomimetic derivatives of the antimalarial drug primaquine (PQ) is reported. These compounds contain the imidazolidin-4-one moiety either at the N- or the C-terminal Of a dipeptide backbone, thus respectively mimicking PQ-Amino Acid-Proline (PQAAPro) and PQProAA derivatives of PQ. Both the peptidomimetics and Precursors previously developed by us are promising drug candidates, as they were found to be active against rodent Plasmodium berghei malaria and pneumocystis carinii pneumonia. Collision-induced dissociation (CID) and tandem-mass spectra (MS) of the title compounds, and fragmentation pathways thereof, led to the following findings: (1) CID patterns present some parallelism with the reactivity towards hydrolysis previously found for the same or related compounds; (2) a positional shift of the imidazolidin-4-one ring is reflected on both degree and pathways of fragmentation, which makes tandem-MS a key tool for differentiation of imidazolidin-4-one isomers; (3) the major MS/MS fragmentation of PQProAA mimetics involves release Of a neutral diketopiperazine (DKP), in parallel to the "diketopiperazine pathway" described in tandem-MS studies of oligopeptides; (4) the relative abundance of a major fragment in tandem-MS spectra is inversely Correlated with the size of the N-terminal AA in PQProAA mimetics. Overall, this work embodies an original and valuable contribution towards a deeper insight into the molecular properties of novel antimalarials, which can be viewed as representative of both the 8-aminoquinoline and, especially, the imidazolidin-4-one structural classes. (J Am Soc Mass spectrom 2008, 19, 1476-1490) (C) 2008 American Society for Mass Spectrometry